Detection of a new apolipoprotein-E mutation in type III hyperlipidemia using deoxyribonucleic acid restriction isotyping - Walden, C C; Huff, M W; Leiter, L A; Connelly, P W; Hegele, R A (The journal of clinical endocrinology and metabolism, 1994)
While determining the apolipoprotein-E (apo-E) genotype of 22 patients with type III hyperlipidemia (HLP III) by restriction isotyping, we identified a new mutant form of apo-E by its unusual DNA restriction fragment length polymorphism pattern. DNA sequence analysis of a polymerase chain reaction-amplified portion of the proband's apo-E gene revealed the substitution of cysteine (TGC) for arginine (CGC) at position 136 in the mutant allele (designated R136C). Lipoproteins containing this mutant protein bound defectively to macrophages in vitro, confirming the contribution of R136C to the expression of HLP III in the proband. The proband's two siblings carried the mutant allele and were also heterozygous for E2. Each also had dysbetalipoproteinemia (indicated by the presence of beta-very low density lipoprotein), but neither was hyperlipidemic, attesting to the importance of other factors for the full expression of HLP III. The mutant allele appears to contribute to the inheritance of HLP III in a recessive fashion. Restriction isotyping facilitates the diagnosis of subjects with HLP III, aids in the identification of affected individuals through family screening, and can contribute to the discovery of new mutations that help explain the pathogenesis of HLP III.